Playing the races : ethnic caricature and American literary realism - Wonham, Henry B., 1960- (Oxford University Press, 2004)
Why did so many of the writers who aligned themselves with the social and aesthetic aims of late 19th-century American literary realism rely on stock conventions of ethnic caricature in their treatment of immigrant African-American figures?